Opportunities and Challenges in Cultivating Underutilized Field Crops in Moneragala District of Sri Lanka - S. H. P, Malkanthi; A. S, Karunaratne; S. D, Amuwala; P, Silva (Asian Journal of Agriculture and Rural Development, 2014)
Cultivation and use of underutilized crops is gradually popularizing in many countries since they create several benefits for the man and the environment. Same as in many other countries, a large number of useful underutilized crop species are available in Sri Lanka as well. Although traditional people had used them in a great deal in many different aspects of their life, the present generation has moved away from using them due to lack of knowledge and interest. In this context, finding of the real potential of cultivating and using them in the country is timely important. Thus the aim of this research is to study the opportunities and challenges of cultivation of underutilized field crops in Sri Lanka. This research is based on the findings of the field survey using 120 farm families in Thanamalwila divisional secretariat division of the Moneragala district during January-October 2012. Results revealed that there are several opportunities such as availability of traditional knowledge, land resource, labor for cultivation etc. However, several constraints like unavailability of seeds and planting materials, lack of market infrastructure, lack of knowledge on processing and value addition, competition from modern crops, negative attitude of consumers are also affecting the cultivation and use of these crops.